A new species of the leafhopper genus Satsumanus Ishihara (Hemiptera: Cicadellidae: Deltocephalinae) from China - Hassan, Muhammad Asghar; Xing, Jichun (Zootaxa, 2024)
Satsumanus Ishihara is a small leafhopper genus in tribe Opsiini with six described species, and each have a very restricted biogeographical distribution in the Australian, Oriental and Palearctic regions. The species Satsumanus satsumae (Matsumura) is recorded for the first time from Zhejiang Province, and a new species Satsumanus discedens sp. nov. is described and illustrated from Guizhou Province, China. The digital photographs of adult male habitus and male genitalia are provided. An updated checklist, global distribution map and taxonomic identification key to known species are provided. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).